2019
DOI: 10.1016/j.aim.2019.106841
|View full text |Cite
|
Sign up to set email alerts
|

The moduli space of Fano manifolds with Kähler–Ricci solitons

Abstract: We construct a canonical Hausdorff complex analytic moduli space of Fano manifolds with Kähler-Ricci solitons. This enlarges the moduli space of Fano manifolds with Kähler-Einstein metrics. We discover a moment map picture for Kähler-Ricci solitons, and give complex analytic charts on the topological space consisting of Kähler-Ricci solitons, by studying differential geometric aspects of this moment map. Some stacky words and arguments on Gromov-Hausdorff convergence help to glue them together in the holomorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…This is the case when X is a smooth Fano manifold, α=2πc1false(Xfalse) corresponds to the anti‐canonical polarization, T Aut red false(Xfalse) is a maximal torus with momentum image normalP, and vfalse(pfalse)=wfalse(pfalse)=eξ,p for some ξt. It was shown recently in that a solutions of with normalw ext false(pfalse)=2false(ξ,p+cfalse) (for some real constant c) corresponds to a Kähler metric ωα which is a gradient Kähler–Ricci soliton with respect to ξ, that is, satisfies Ric false(ωfalse)ω=12scriptLJξω,where Ric (ω) is the Ricci form of ω. Thus, the theory of gradient Kähler–Ricci solitons (see, for example, ) fits in to our setting too.…”
Section: Examplesmentioning
confidence: 99%
“…This is the case when X is a smooth Fano manifold, α=2πc1false(Xfalse) corresponds to the anti‐canonical polarization, T Aut red false(Xfalse) is a maximal torus with momentum image normalP, and vfalse(pfalse)=wfalse(pfalse)=eξ,p for some ξt. It was shown recently in that a solutions of with normalw ext false(pfalse)=2false(ξ,p+cfalse) (for some real constant c) corresponds to a Kähler metric ωα which is a gradient Kähler–Ricci soliton with respect to ξ, that is, satisfies Ric false(ωfalse)ω=12scriptLJξω,where Ric (ω) is the Ricci form of ω. Thus, the theory of gradient Kähler–Ricci solitons (see, for example, ) fits in to our setting too.…”
Section: Examplesmentioning
confidence: 99%
“…After establishing this theorem, we can apply it to study the deformation space of Eiji Inoue [10], which is the same as the definition of the kernel space of second order variation of Perelman's entropy [16]. We will prove: Theorem 0.2.…”
Section: Introductionmentioning
confidence: 95%
“…For polarised Kähler manifolds, there is an algebraic notion of stability, K-stability, which is conjecturally equivalent by the Yau-Tian-Donaldson conjecture to the existence of cscK metrics [38,36,13]. It has been proved that it is possible to form an analytic moduli space of cscK manifolds [18,5]; see also [26].…”
Section: Scal(ωmentioning
confidence: 99%
“…We will later need to choose ω B appropriately, to produce cscK and extremal metrics on Y . To do so, we need the following definitions from the moduli theory of cscK manifolds [18,26,5]. In [5] it is shown that there exists a complex space M which is the moduli space of polarised cscK manifolds and that there exists a Kähler metric on M called the Weil-Petersson metric.…”
Section: Extremal Metrics On the Total Spacementioning
confidence: 99%